Evidence-Based Practice in Education: Tools for Assessing Learning in the Context of Innovation - N. A. Lyz’; O. N. Istratova; E. V. Golubeva (Высшее образование в России)
Higher education is developing and becoming diverse, flexible, and innovative. Innovations affect both organizational formats and programs, and the educational process. Under these conditions, for the operational management of learning and pedagogical innovations, it is necessary to monitor not only the results, but also the procedural characteristics of education, which allow us to draw conclusions about the educational process effectiveness. The three-level model of factors influencing learning outcomes presented in the article showed that it is most important to analyze the learning process from the position of the student as its subject. It is the activities of students and their educational experience, that firstly, act as a direct factor of the effectiveness of this process, and secondly, they are sensitive to changes in learning technologies and teaching practices used. Students’ activities and experience are conceptualized and measured in terms of various constructs, the most common of which are: learning activity, self-regulated learning, engagement, satisfaction, educational experience. The article systematizes approaches to diagnosing relevant variables and characterizes domestic verified questionnaires for their measurement. The author’s short questionnaire is proposed to study the educational experience of students: their involvement, satisfaction, self-regulation, self-efficacy and intentions for development. The described questionnaires can be used to analyze the learning attainment and build evidence-based practices in higher education, as well as a source of data for predicting the learning outcomes.